To Evaluate the Impact of Web Series on the Manas Bhava (Psychological Well-Being) of Adolescent Students - Akash Sachan; Madhulika D Tiwari (International Journal of Ayurveda and Pharma Research, 2025)
Despite age limitations not applying to web series, their consumption has surged, especially among users under 35 years of age. In light of Ayurvedic principles, excessive use of sensory organs (Asatmya indriya sanyog) may impact “Manas bhava” (mental disposition) and lead to “Manas vikaar” (mental disorders). This study aims to explore the psychological effects of OTT web series on Adolescents through an online survey. Aims and Objectives: To evaluate the impact of online web series on the Manas bhava (psychological well-being) of Adolescents. Methodology: We conducted a questionnaire based survey exclusively designed to “Evaluate the status of Manas bhava” for investigating how online series affect manas bhava or psychological well-being amongst adolescents. Following data collection, observation and result were drawn based on the questionnaire. Statistical analysis of the data in percentage was drawn to conclude the significant changes seen in the Manas bhava (psychological well-being). Observation and Result: Empirical evidence indicates that prolonged exposure to online series, particularly those characterized by excitement and action, adversely impacts the Manas bhava (psychological well-being) of adolescent students. Conclusion- In the context of mental health, Manas vikar refers to psychological disorders. The study findings indicate that 37% of students experience mild stages of Manas vikar, which can be likened to depression, while 11% exhibit more severe conditions (Vyaktavastha). These results emphasize the need to address mental health concerns among adolescents, especially in relation to their consumption of OTT web series. To better understand the impact of web series on adolescent mental well-being, a multidisciplinary approach that includes fostering media literacy and promoting mindful consumption is essential.